Sensorial characteristics of a diet and conventional fig compote - Caetano, Priscilla Kárim [UNESP]; Daiuto, Érica Regina [UNESP]; Vieites, Rogério Lopes [UNESP]; De Garcia, Aline Oliveira [UNESP]; Smith, Robert E. (Bentham Science Publishers, 2015)
The goal of this project was to develop a low calorie fig compote (diet and conventional) through sensorial analysis. It was made from red figs and sweeteners. Three replicates of nine different formulations were tested. They contained 330 g of figs and 265 g of sweeteners containing 2.66 g citric acid, 707 mL of water and various amounts of either sucrose; sorbitol; erythritol; sorbitol plus erythritol; steviosíde; sodium cyclamate, sucralose plus sodium saccharine; sodium cyclamate plus sodium saccharine; acesulfame-K plus sucrose; and steviosíde plus sodium saccharine plus sodium cyclamate. The samples were analyzed for coliform bacteria, pH and sensorial properties. The sensorial analyses of figs included tests for aroma, flavor, sweetness, acidity and texture. The compotes were evaluated for initial flavor, sweetness, consistency, flavor that remained in the mouth, overall evaluation and residual flavor. There were no signs of bacterial contamination and the pH varied from 3.89 to 4.47. The sensorial tests found that the compotes made from sodium cyclamate, sucralose plus sodium saccharine as well as stevioside plus sodium cyclamate plus sodium saccharine were as good as the one made from just sucrose. The fig compote made from sodium cyclamate plus sucralose and sodium saccharine was given the name diet and conventional. It had sensorial values similar to the compote made from sucrose.
Keywords: Ficus carica L; Fig; Sodium cyclamate; Sodium saccharine; Stevioside; Sucralose